•
(
n
ln
----------------------------------------------------------------- -
B =
•
n
------------------------------------------------------------------------------------------------------------------
=
r
{
•
(
n
–
y A
----------- -
x ˆ
B
=
e
y ˆ
= A + Blnx
e Exponentiële regressie (e^ X)
Bx
y = Ae
ln
------------------------------------- -
exp
A =
•
n
x y
ln
------------------------------------------------------------ -
B =
•
n
------------------------------------------------------------------------------------------------------------------
=
r
{
•
n
x
–
ln
y
ln
A
x ˆ
-----------------------
=
B
y ˆ
Bx
=
Ae
ab Exponentiële regressie (A
X
y = AB
ln
------------------------------------- -
exp
A =
•
n
x y
------------------------------------------------------------ -
B =
•
n
------------------------------------------------------------------------------------------------------------------
=
r
{
•
n
x
–
ln
ln
y
A
x ˆ
-----------------------
=
B
)y
–
x
ln
x
2
(
)
–
(
ln
x
ln
•
(
)y
ln
n
x
2
)
–
(
ln
x
ln
–
•
y
B
x
n
–
•
x
2
2
–
(
)
x
x
•
ln
n
x y
2
2
–
(
)
} n
{
x
–
•
y
B
x
n
–
•
ln
x
2
2
–
(
)
x
x
•
ln
n
x y
2
2
–
(
)
} n
{
x
y ˆ
= ABx
•
y
2
)
x
–
•
ln
x
2
2
)
} n
{
•
x
y
ln
y
–
•
ln
x
y
2
•
(
)
–
ln
y
⋅
B^X)
ln
y
–
•
ln
x
y
2
•
(
)
–
ln
y
62
y
2
–
(
)
}
y
2
(
)
}
ln
y
2
(
)
}
ln
y